O calabouço cotidiano na vida dos trabalhadores assalariados: os grilhões que entrelaçam o tempo, fora e dentro da indústria - Camargo, William Silvano de (2016)
The capital-labor contradiction, consolidated in bourgeois society, is essential to elaborate an analysis that deals with aspects of the work and its measurement - the time - in the capitalist mode of production. The understanding of work and time becomes dull by reason of the very alienation that workers suffer on the ideological imposition of the bourgeoisie class. This present study aims to analyze the labor relations and workers inside and outside the factory. So our research object is explicit in labor relations and time built by workers, inside and outside a rattlesnake packaging industry. Our purpose to be achieved while General purpose envisioned in: learn, understand and analyze the relations between capital and labor in a packaging industry relating the trapped time and free time. It is in this universe that problematize the following question: The worker, after completing his workday stipulated by the labor contract, does business in his spare time, which is present content that leads you to live moments of human emancipation? To pursue and respond to the problem presented, the outline of this thesis is structured as follows. Chapter 1: Work and Productions modes will address the social and technical divisions of labor to the contemporary. Chapter 2: The apogee of capitalism and the Industrial Revolution will travel on capitalism's domain elements of the working class as an example the production models. Chapter 3: Here is the empirical research with the workers of Papeon packaging industry in Cascavel-PR. In this chapter the research will examine the time in and out of the workspace in the workers' daily lives, analyzing aspects of employee relations and machine and capitalist exploitation in the factory and spaces and opportunities to experience time out of the factory. The end result of the research brought the following concluding summary: Workers in the spaces outside of work, replenish your energies to return to work because the conditions to exercise their human emancipatory materialities are not found in everyday life.